Retracted: Design and Performance Evaluation of OAM-Antennas: A Comparative Review - Omar A. Saraereh (IEEE Access)
For many communication systems, including wireless networks, mobile, satellite, radar, remote sensing, and many more applications, antenna arrays are very necessary. Utilizing effective beamforming techniques, antenna arrays have recently played a major part in driving data rates and system capacity to extremely high levels. The beamforming capabilities and system performance are both greatly influenced by the array configuration. Numerous array structures, including linear, two-dimensional, circular, conical, cylindrical, spherical, and even non-uniform array shapes, can be used in different applications. Modern communication systems pay a lot of attention to reconfigurable antennas because of the many applications they may serve and the added functionality they provide. A single structure that has the ability to change between one or a number of features, such as frequency, pattern, and polarization, is referred to as a reconfigurable antenna. Utilizing a specific circular phased microstrip antenna array, the orbital angular moment (OAM) vortex electromagnetic wave is created, allowing for more effective and dependable data transmission. When propagating, the vortex electromagnetic wave has a spiral phase wavefront structure, and its many OAM modes are orthogonal to one another. The helical antenna offers the benefits of light weight, small size, and excellent circular polarization when compared to other OAM radio producing techniques. This paper reviews various state-of-the-art antennas for 5G applications. Specifically, the single microstrip, array, traveling wave and metasurface antennas have been discussed and their important aspects were elaborated. Finally, the applications and future prospects were described.